Recoverable polymer aerogel, cold-storage phase-change composite material, and preparation method and application of cold-storage phase-change composite material
Patent Information
- Application Number
- CN202380064050.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-09
- Filing Date
- 2023-09-08
- Publication Date
- 2025-04-11
AI Technical Summary
There are environmental pollution problems in the preparation process of existing polymer aerogels, and they are difficult to recycle, especially cross-linked aerogels, which limits their industrial application; at the same time, organic phase change materials have leakage risks and resources in energy storage applications. Waste problem.
Use polymer raw materials containing maleic anhydride and maleimide groups to prepare aerogels in ammonia water, obtain hydrophobic and water-resistant aerogels through heat treatment, and achieve efficient recovery in ammonia water, avoiding the use of organic solvents, and develop The cold storage phase change composite material can be recycled to reduce leakage and introduce real-time temperature monitoring capabilities into the material.
It achieves the preparation and recycling of low-pollution, green and environmentally friendly polymer aerogels. It is a recyclable cold storage phase change composite material with high recycling efficiency and low leakage. It is suitable for a variety of application fields and has real-time temperature monitoring functions.
Smart Images

Figure CN119816561A_ABST
Abstract
Description
Recyclable polymer aerogel, cold storage phase change composite material, preparation method and application Technical Field
[0001] The present invention relates to the field of porous materials, and in particular to a recyclable polymer aerogel, a preparation method, a recycling method, and an application thereof; as well as a recyclable cold storage phase change composite material comprising the recyclable polymer aerogel, a recyclable cold storage phase change material with a real-time temperature monitoring function, and a preparation method and application thereof. Background Art
[0002] Polymer aerogels are a new type of lightweight solid material composed of clusters of colloidal particles or polymer molecules, with a three-dimensional porous structure and a network of pores filled with a gas dispersion medium. They feature low density, high porosity, and a large specific surface area. They also possess high-temperature resistance, low thermal conductivity, and a low refractive index. They are currently widely used in thermal and acoustic insulation, adsorption and separation, catalysis, energy storage and conversion, sound absorption and sound insulation, sensor platforms, anti-fouling and anti-sticking materials, waterproof fabrics, and proton exchange membranes.
[0003] Polymer aerogels are typically prepared using sol-gel and phase separation methods. The sol-gel method requires at least three steps: solution-to-sol conversion, sol-to-gel conversion, and gel-to-aerogel conversion, and requires an extremely time-consuming aging process of up to 6-7 days. The phase separation method first uses an organic solvent to create a polymer solution. After gelation, the organic solvent is then replaced with water to form a hydrogel, which is then used to produce an aerogel. However, this method has the disadvantage of requiring the handling of large amounts of organic solvent. Polymer aerogels can also be prepared directly from aqueous solutions, but this requires crosslinking and hydrophobic post-treatment of the aerogel product, making the process more complex. Clearly, polymer aerogels, especially crosslinked low-density polymer aerogels, not only pose environmental risks during their preparation, but also make the products difficult to recycle. Therefore, as consumption increases, polymer aerogels will generate even more severe "white pollution" than conventional plastic products, hindering their industrial application. Clearly, developing low-pollution, recyclable polymer aerogels is a pressing technical challenge in aerogel technology.
[0004] To achieve hydrophobicity and water resistance, polymer aerogels prepared in existing technologies often require crosslinking and hydrophobization. These crosslinked aerogels are extremely difficult to recycle. Therefore, creating hydrophobic and water-resistant aerogels without crosslinking is the best approach to achieving aerogel recyclability. However, the preparation and recycling of hydrophobic aerogels typically requires the use of large amounts of organic solvents, which introduces new pollution risks.
[0005] In recent years, the demand for cold energy has rapidly increased, making low-temperature energy storage extremely attractive. There are two common cooling methods: active cooling, such as electrical refrigeration and freezing equipment like refrigerators and freezers; and passive cooling, such as coolers, cooler bags, and ice boxes that utilize phase change materials to store cold. Active cooling methods like refrigerators are relatively expensive, and controlling and reducing consumption and improving system efficiency have become top priorities for researchers in this field. Passive cooling methods, such as coolers and phase change materials, can utilize nighttime "low-peak" electricity or green energy like solar energy to store cold, and thus offer great potential. Among the many energy storage technologies, methods utilizing solid-liquid transitions based on phase change materials to store large amounts of energy have been explored in various cooling applications, such as food storage, transportation, and air conditioning. Phase change materials offer a compact and feasible solution to address the imbalance between supply and demand, due to their high energy storage density. Phase change materials are primarily categorized as organic and inorganic. Compared to inorganic phase change materials, organic phase change materials have attracted more attention in practical applications due to their advantages such as non-toxicity, minimal supercooling, and excellent cyclic stability. However, organic phase change materials face the risk of leakage when used directly as energy storage materials. Therefore, encapsulation of the phase change materials is essential to prevent leakage. Furthermore, organic phase change materials also need to be reprocessable and recyclable to avoid environmental pollution and resource waste.
[0006] Therefore, how to provide a hydrophobic aerogel that is both hydrophobic and water-resistant and can be easily and environmentally friendly recycled, and how to provide a recyclable cold storage phase change composite material with low leakage and recyclability based on the above aerogel, are technical challenges that need to be solved at present.
[0007] Summary of the Invention
[0008] In response to the technical problems existing in the prior art, the present invention provides a recyclable polymer aerogel, its preparation method, recycling method, and application. For the first time, a polymer containing a maleimide-containing structural unit is prepared into an aerogel, broadening the application range of copolymers containing maleic anhydride- and maleimide-containing structural units. More importantly, the aerogel prepared by the present invention has an extremely high recovery efficiency, exceeding 99% after dissolution and recovery using ammonia water. The aerogel preparation and recycling process does not require the use of any organic solvents, resulting in low energy consumption, high efficiency, and environmental friendliness. Furthermore, the polymer aerogel of the present invention has excellent hydrophobic and water-resistant properties, low thermal conductivity, low density, and good heat resistance, making it suitable for use in a variety of fields and possessing extremely high application value.
[0009] The inventors of the present invention have found in their research that when a copolymer with maleic anhydride and its derivative groups, such as one or more polymer raw materials containing structural units containing maleic anhydride, maleimide, maleic acid and ammonium salt, maleamic acid and ammonium salt groups, is dissolved in ammonia, a polymer aqueous solution can be obtained. After freeze drying, a copolymer aerogel containing maleic anhydride groups and maleimide groups with hydrophobic and water-resistant properties is prepared by heat treatment. Due to the strong hydrogen bonding between the functional groups of maleic acid and its ammonium salt, maleamic acid and its ammonium salt, maleic anhydride and maleimide, the three-dimensional pore structure of the aerogel is kept stable during the heat treatment process, and a hydrophobic and water-resistant polymer aerogel is obtained under the conditions of not needing to be cross-linked and hydrophobized, which is environmentally friendly and reduces the time and material cost of preparation. The polymer aerogel prepared by the method of the present invention can be recycled under the action of ammonia, and the special properties of this type of polymer can be used to realize repeated conversion of water-soluble polymers and water-resistant hydrophobic aerogels, and the above process does not need to use organic solvents, which is more environmentally friendly.
[0010] Based on the above-mentioned recyclable polymer aerogel, the present invention also provides a recyclable cold storage phase change composite material, its preparation method, and application. This recyclable cold storage phase change composite material not only has cold storage capacity, but is also recyclable and has low leakage. Furthermore, the present invention further provides a recyclable cold storage phase change composite material with real-time temperature monitoring. This composite material not only has cold storage capacity, is recyclable, has low leakage, but also has real-time temperature monitoring.
[0011] The first aspect of the present invention is to provide a polymer aerogel, wherein the polymer contains a structural unit containing a maleic anhydride group and a structural unit containing a maleimide group.
[0012] According to the present invention, a maleic anhydride group refers to The maleimide group refers to
[0013] According to the invention, the polymers are carbon chain polymers in which the heteroatoms O and N are present in side groups.
[0014] In a preferred embodiment of the present invention, based on the total molar amount of the structural units containing maleic anhydride groups and the structural units containing maleimide groups as 100%, the molar ratio of the structural units containing maleimide groups in the polymer is 5%-70%, preferably 10%-60%; more preferably 20%-50%, for example, 20%, 25%, 30%, 35%, 40%, 45%, 50%, and any two values or any interval between any two values.
[0015] According to the present invention, the polymer can be selected from a wide range. In a preferred embodiment of the present invention, the polymer is derived from one or more polymer raw materials containing structural units containing maleic anhydride, maleimide, maleic acid and ammonium salt, maleamic acid and ammonium salt groups.
[0016] The maleic anhydride group refers to The maleimide group refers to Maleic acid and ammonium salt groups, maleamic acid and ammonium salt groups refer to Wherein M is the same or different and each is hydroxyl, amino or ammonium (-ONH4).
[0017] According to the invention, the polymers are carbon chain polymers in which the heteroatoms O and N are present in side groups.
[0018] In the present invention, the polymer raw materials include, but are not limited to, copolymers of one or more monomers selected from maleic anhydride, maleimide, maleic acid and ammonium salts, or maleamic acid and ammonium salts, and olefin monomers. For example, the present invention can also be achieved when the polymer raw materials are styrene-maleic anhydride-vinyl silicone oil copolymers. Copolymers of one or more monomers selected from maleic anhydride, maleimide, maleic acid and ammonium salts, or maleamic acid and ammonium salts, and olefin monomers have lower raw material costs.
[0019] Preferably, the polymer raw material is a copolymer of one or more monomers selected from the group consisting of maleic anhydride, maleimide, maleic acid and its ammonium salt, or maleamic acid and its ammonium salt, and an olefin monomer; more preferably, the olefin monomer is at least one of α-methylstyrene, styrene, isobutylene, and vinyl acetate. More preferably, the polymer raw material is an alternating copolymer of one or more monomers selected from the group consisting of maleic anhydride, maleimide, maleic acid and its ammonium salt, or maleamic acid and its ammonium salt, and one of α-methylstyrene, styrene, and isobutylene.
[0020] By way of example, the polymer raw material in the present invention includes, but is not limited to, at least one of styrene-maleic anhydride copolymer, styrene-maleic anhydride-vinyl silicone oil copolymer, and maleic anhydride-isobutylene copolymer. Preferably, the polymer raw material in the present invention includes at least one of styrene-maleic anhydride copolymer and maleic anhydride-isobutylene copolymer.
[0021] In a preferred embodiment of the present invention, the polymer aerogel can be dissolved in ammonia water at 0-150°C to form a polymer aqueous solution. Preferably, the polymer aqueous solution can be recovered by pre-freezing, freeze-drying, and heat-treating to obtain the polymer aerogel. Therefore, the polymer aerogel of the present invention can be conveniently and environmentally friendly recycled.
[0022] In a preferred embodiment of the present invention, the thermal conductivity of the polymer aerogel is 0.025-0.05 W / (m·k), preferably 0.027-0.04 W / (m·k). The polymer aerogel of the present invention has the characteristic of low thermal conductivity and can be used directly as a thermal insulation material without any treatment.
[0023] In a preferred embodiment of the present invention, the density of the polymer aerogel is 10-100 kg / m 3 , preferably 15-75kg / m 3 Specifically, for example, 15 kg / m 3 、35kg / m 3 , 45kg / m 3 , 55kg / m 3 、65kg / m 3 , 75kg / m 3 , and any two values or any range between any two values; and / or, the polymer aerogel is a porous material. The polymer aerogel of the present invention has high porosity and is a three-dimensional porous material that can be used as a carrier. For example, it can be used as a skeleton to support an organic phase change material, preventing leakage of the phase change material. The prepared phase change composite material can also be recovered using ammonia solution.
[0024] The inventors of the present invention have discovered that the polymer aerogel, when it is a styrene-maleic anhydride-maleimide copolymer aerogel, also exhibits photoluminescence, with the light signal changing with temperature. The photoluminescence properties of this type of polymer aerogel can also be used as an indicator material to display temperature changes.
[0025] In a preferred embodiment of the present invention, the static water contact angle of the polymer aerogel is above 100°, preferably above 110°, and more preferably above 135°.
[0026] In a preferred embodiment of the present invention, the polymer aerogel is insoluble in water. Preferably, the polymer aerogel does not dissolve to form an aqueous polymer solution after immersion in water at 20-40°C for 24 hours, preferably 72 hours, and more preferably 168 hours. The polymer aerogel of the present invention exhibits both superlipophilicity and hydrophobicity and can be used directly as an oil-water separation material without any further treatment.
[0027] In a preferred embodiment of the present invention, the polymer aerogel is prepared by reacting one or more polymer raw materials containing structural units containing maleic anhydride, maleimide, maleic acid and ammonium salt, maleamic acid and ammonium salt groups with ammonia water in a closed environment, and then pre-freezing, freeze-drying, and heat treatment for dehydration and deamination.
[0028] According to the present invention, the polymer aerogel in the present invention can be an anisotropic aerogel or an isotropic aerogel.
[0029] The difference between anisotropic aerogel and isotropic aerogel is the pore structure. The pore structure of anisotropic aerogel shows long-range order, mainly because the ice crystals grow in a directional manner during the pre-freezing stage of the aerogel, and impurities (polymers in the present invention) are expelled during the growth process. The impurities gather to form pore walls; the subsequent freeze-drying, that is, removing the ice, obtains a porous aerogel. Therefore, anisotropic aerogels can be obtained by using different unidirectional cold source temperatures during pre-freezing. There are many options for implementing the unidirectional cold source temperature, including but not limited to using liquid nitrogen as a low-temperature cold source during pre-freezing, placing the mold on a copper column immersed in liquid nitrogen, and ice crystals growing upward from the bottom of the mold, eventually forming an aerogel with an anisotropic pore structure.
[0030] Anisotropic aerogels have different pore structures, different axial and radial thermal conductivities, and different material and sound transmission rates. Anisotropic and isotropic aerogels can be selected based on different applications. For example, when encapsulating phase change materials in the present invention, the inventors discovered that using the preferred anisotropic aerogel significantly reduced leakage, regardless of the orientation of the anisotropic aerogel.
[0031] A second aspect of the present invention provides a method for preparing a polymer aerogel, comprising reacting a polymer raw material containing one or more structural units selected from the group consisting of maleic anhydride, maleimide, maleic acid and ammonium salt, and maleamic acid and ammonium salt with aqueous ammonia under closed conditions, followed by pre-freezing, freeze-drying, and heat treatment for dehydration and deamination to obtain the polymer aerogel.
[0032] The aerogel preparation method of the present invention only requires heat treatment of the water-soluble aerogel, avoiding the need for introducing a crosslinking agent or performing a hydrophobic treatment to produce a hydrophobic and water-resistant aerogel. The preparation method is simple, easy, and environmentally friendly, and is applicable to the preparation of various maleimide copolymer aerogels. No crosslinking agent is added in the aerogel preparation method of the present invention.
[0033] In a preferred embodiment of the present invention, the preparation method comprises the following specific steps:
[0034] (1) reacting the polymer raw material with ammonia water under closed conditions to obtain a polymer aqueous solution;
[0035] (2) pre-freezing the polymer aqueous solution obtained in step (1) and then freeze-drying it to obtain a water-soluble polymer (i.e., a polymer aerogel precursor);
[0036] (3) heat-treating the water-soluble polymer obtained in step (2) to obtain the polymer aerogel.
[0037] According to the present invention, the amount of polymer raw material and ammonia water in step (1) can be selected within a wide range. In a preferred embodiment of the present invention, in step (1):
[0038] Based on the total mass of the reaction system as 100%, the mass fraction of the polymer raw material used is 0.1%-30%, preferably 0.5%-10%, more preferably 1%-5%. Based on the mass of ammonia in ammonia water, the mass fraction of ammonia used is 0%-30%, preferably 0.01%-10%, more preferably 0.1%-1%. The remaining components are water.
[0039] According to the present invention, the reaction conditions in step (1) can be selected within a wide range. In a preferred embodiment of the present invention, the reaction conditions include: a reaction temperature of 0-200° C., preferably 50-150° C., more preferably 80-100° C., and / or a reaction time of 0.01-100 h, preferably 0.5-10 h, more preferably 1-5 h. The reaction pressure is not particularly limited, but is preferably carried out under normal pressure.
[0040] In a preferred embodiment of the present invention, step (2) comprises pre-freezing the aqueous polymer solution obtained in step (1) in a mold to obtain ice cubes. The mold can be of any shape and size and can be customized according to the desired aerogel. Freezing can be performed using a cold source such as a refrigerator or liquid nitrogen.
[0041] The cooling source temperatures of the aqueous solution in all directions during the pre-freezing are the same or different. If the cooling source temperatures of the mixed solution in all directions during the pre-freezing are consistent, the aerogel prepared is isotropic. If the cooling source temperatures of the aqueous solution in all directions during the pre-freezing are different, anisotropic aerogel can be prepared. Preferably, the cooling source temperatures in one direction during the pre-freezing are different to obtain anisotropic aerogel. There are many options for implementing the one-way cooling source temperature, including but not limited to using liquid nitrogen as the low-temperature cooling source during pre-freezing, placing the mold on a copper column immersed in liquid nitrogen, and allowing ice crystals to grow upward from the bottom of the mold.
[0042] Specifically, the pre-freezing conditions may be conventional temperature conditions in the art, and the present invention has no particular limitation.
[0043] According to the present invention, the freeze-drying conditions can be selected within a wide range, and the present invention is not particularly limited. In a preferred embodiment of the present invention, the freeze-drying conditions include: a temperature of below -10°C, for example, below -20°C, or below -30°C. According to the present invention, the vacuum degree of freeze-drying can be selected within a wide range. In a preferred embodiment of the present invention, the vacuum degree is below 1000 Pa, for example, below 100 Pa, or below 10 Pa. The above freeze-drying conditions can be flexibly selected based on cost, efficiency, and the conventional operation mode of the equipment.
[0044] The freeze drying process can adopt various freeze drying equipment in the prior art, such as freeze dryer, freeze spray dryer, industrial freeze dryer, etc.
[0045] According to the present invention, the conditions for the heat treatment in step (3) can be selected within a wide range. In a preferred embodiment of the present invention, the conditions for the heat treatment in step (3) include: a temperature of 100-300°C, preferably 130-200°C, more preferably 150-190°C, and / or a time of 0.1-10h, preferably 0.5-3h, more preferably 1-2h.
[0046] In a preferred embodiment of the present invention, the polymer raw material can react with ammonia water to obtain a water-soluble polymer.
[0047] According to the present invention, the polymer raw material can be selected from a wide range. In a preferred embodiment of the present invention, the polymer raw material is a polymer containing one or more structural units containing maleic anhydride, maleimide, maleic acid and ammonium salt, maleamic acid and ammonium salt groups; preferably, the polymer raw material is a copolymer of one or more polymerization monomers including maleic anhydride, maleimide, maleic acid and ammonium salt, maleamic acid and ammonium salt and an olefin monomer; more preferably, the olefin monomer includes at least one of α-methylstyrene, styrene, and isobutylene.
[0048] For example, the polymer raw material includes but is not limited to at least one of styrene maleic anhydride copolymer, styrene maleic anhydride vinyl silicone oil copolymer, and maleic anhydride isobutylene copolymer. Preferably, the polymer raw material includes at least one of styrene maleic anhydride copolymer and maleic anhydride isobutylene copolymer.
[0049] More specifically, the preparation process of the polymer aerogel of the present invention includes the following steps: a. reacting a polymer raw material containing one or more structural units selected from the group consisting of maleic anhydride, maleimide, maleic acid and ammonium salt, or maleamic acid and ammonium salt with ammonia water in a sealed container and heating the reaction to prepare a polymer aqueous solution; b. pouring the polymer aqueous solution into a mold, pre-freezing the mold until it is completely frozen into ice cubes, and then freeze-drying the mold in a freeze dryer for a predetermined period of time to obtain a water-soluble polymer; and c. heat-treating the water-soluble polymer under constant temperature conditions to dehydrate and deaminate the polymer to obtain a water-resistant maleimide-based aerogel.
[0050] The polymer raw materials mentioned above are all polymers disclosed in the prior art, and can be commercially available from the prior art, or prepared according to the methods disclosed in the prior art.
[0051] In the present invention, there is no particular limitation on the material of the sealed container, which may be made of metal, non-metal, polymer or other materials.
[0052] The “and / or” involved in the present invention means that the two conditions before and after “and / or” can be selected one by one, or the two conditions can exist at the same time.
[0053] A third aspect of the present invention provides a method for recovering polymer aerogels, wherein the polymer aerogels are those described in the first aspect or those prepared by the preparation method described in the second aspect. The recovery method comprises mixing the polymer aerogels and / or materials containing the polymer aerogels with aqueous ammonia under closed conditions until an aqueous solution containing the recovered polymer is obtained, and optionally removing insoluble matter to obtain an aqueous solution of the recovered polymer. This aerogel recovery method does not require the introduction of organic solvents or high-temperature, high-pressure stirring processes. It only requires a certain concentration of aqueous ammonia, preferably maintained below 100 degrees Celsius, enabling rapid and efficient recovery. This method has low energy consumption, minimal pollution, and high efficiency. The recovered polymer solution can be reused in the preparation of polymer aerogels.
[0054] The polymer aerogel recovery method of the present invention comprises placing the polymer aerogel in ammonia water of a certain concentration, placing the polymer aerogel in a sealed container, heating the aerogel at a certain temperature, and waiting for the aerogel to be completely dissolved to obtain a copolymer aqueous solution.
[0055] According to the present invention, the conditions for the mixed reaction in the recovery method can be selected within a wide range. In a preferred embodiment of the present invention, the mixed reaction temperature is 0-200° C., preferably 50-150° C., more preferably 80-100° C., and / or the mixed reaction time is 0.01-100 h, preferably 0.5-10 h, more preferably 1-5 h. The reaction pressure is not particularly limited, but is preferably carried out under normal pressure.
[0056] In a preferred embodiment of the present invention, the recovery method further comprises pre-freezing, freeze-drying, and heat-treating the aqueous solution of the recovered polymer to recover the polymer aerogel.
[0057] According to the present invention, the temperature of the cooling source in each direction of the aqueous solution during pre-freezing is the same or different. If the temperature of the cooling source in each direction of the aqueous solution during pre-freezing is consistent, the prepared aerogel is isotropic; if the temperature of the cooling source in each direction of the aqueous solution during pre-freezing is different, anisotropic aerogel can be prepared. Preferably, the temperature of the cooling source in one direction during pre-freezing is different to obtain anisotropic aerogel. There are many options for implementing the temperature of the one-way cooling source, including but not limited to using liquid nitrogen as a low-temperature cooling source during pre-freezing, placing the mold on a copper column immersed in liquid nitrogen, and allowing ice crystals to grow upward from the bottom of the mold.
[0058] According to the present invention, the freeze-drying conditions can be selected within a wide range, and the present invention is not particularly limited. In a preferred embodiment of the present invention, the freeze-drying conditions include: a temperature of below -10°C, for example, below -20°C, or below -30°C, and / or a vacuum degree of below 1000 Pa, for example, below 100 Pa, or below 10 Pa.
[0059] According to the present invention, the conditions for heat treatment can be selected within a wide range. In a preferred embodiment of the present invention, the conditions for heat treatment include:
[0060] The temperature is 100-300° C., preferably 130-200° C., more preferably 150-190° C. and / or the time is 0.1-10 h, preferably 0.5-3 h, more preferably 1-2 h.
[0061] The fourth aspect of the present invention provides a recycled polymer aerogel obtained by the recycling method according to the third aspect.
[0062] The polymer aerogel obtained by the above method has properties comparable to those of the polymer aerogel prepared initially and can be recycled.
[0063] A fifth aspect of the present invention provides the use of the polymer aerogel described in the first aspect, the polymer aerogel prepared by the preparation method described in the second aspect, or the recycled polymer aerogel described in the fourth aspect as a porous material, preferably as a carrier, a filter material, for adsorbing organic phase change materials, or as an oil-water separation material or thermal insulation material. When used as a porous material, the polymer aerogel can serve as a support material, such as a phase change material, to prevent leakage.
[0064] The hydrophobic polymer aerogel described in the present invention can be used for oil-water separation without surface treatment and can be used as a thermal insulation aerogel. It can also be blended with other components to prepare multi-component aerogel. When other components are insoluble in ammonia water, the multi-component aerogel can also be recovered by ammonia water.
[0065] The sixth aspect of the present invention is to provide a recyclable cold storage phase change composite material, comprising a polymer aerogel and a phase change material loaded in the polymer aerogel; wherein the polymer aerogel is the polymer aerogel described in the first aspect, the polymer aerogel prepared by the preparation method described in the second aspect, or the recycled polymer aerogel described in the fourth aspect.
[0066] According to the present invention, the content of phase change material and polymer aerogel in the recyclable cold storage phase change composite material can be selected within a wide range. In a preferred embodiment of the present invention, based on the total mass of the recyclable cold storage phase change composite material as 100%, the content of the polymer aerogel is 2%-20%, preferably 4%-10%, for example, it can be 4%, 5%, 6%, 7%, 8%, 9%, 10%, and any two values or any interval between any two values; the content of the phase change material is 80%-98%, preferably 90%-96%.
[0067] Preferably, the total mass of the polymer aerogel and the phase change material is 100%.
[0068] According to the present invention, the phase change material can be selected within a wide range, as long as it has cold storage performance. The phase change material includes but is not limited to an organic phase change material. Preferably, the organic phase change material has a phase change temperature of (-10)-30°C, and / or a phase change latent heat of 55-280 J / g; more preferably, it is an alkane organic phase change material, and even more preferably, it is at least one of decane, dodecane, and tetradecane.
[0069] In a preferred embodiment of the present invention, under the temperature condition that the phase change material is liquid, the leakage amount of the phase change material in the recyclable cold storage phase change composite material is less than 10 wt%, preferably less than 5 wt%, and more preferably less than 2 wt%.
[0070] According to the present invention, the polymer aerogel in the cold storage phase change composite material can be an anisotropic aerogel or an isotropic aerogel.
[0071] The difference between anisotropic aerogel and isotropic aerogel is the pore structure. The pore structure of anisotropic aerogel shows long-range order, mainly because the ice crystals grow in a directional manner during the pre-freezing stage of the aerogel, and the impurities (polymers in the present invention) are expelled during the growth process. The impurities gather to form pore walls; the subsequent freeze drying, that is, the removal of ice, obtains a porous aerogel. Therefore, anisotropic aerogels can be obtained by using different unidirectional cold source temperatures during pre-freezing. There are many options for implementing the unidirectional cold source temperature, including but not limited to using liquid nitrogen as a low-temperature cold source during pre-freezing, placing the pre-freezing container on a copper column immersed in liquid nitrogen, and ice crystals growing upward from the bottom of the pre-freezing container, eventually forming an aerogel with an anisotropic pore structure.
[0072] Anisotropic aerogels have different pore structures, different axial and radial thermal conductivities, and different material and sound transmission rates. Anisotropic and isotropic aerogels can be selected based on different applications. For example, when encapsulating phase change materials in the present invention, the inventors discovered that using the preferred anisotropic aerogel significantly reduced leakage, regardless of the orientation of the anisotropic aerogel.
[0073] In a preferred embodiment of the present invention, the polymer aerogel in the cold storage phase change composite material is an anisotropic aerogel, preferably an anisotropic aerogel obtained by applying different temperatures to a unidirectional cold source during pre-freezing. In this preferred embodiment, under temperature conditions where the phase change material is liquid, leakage of the phase change material in the recyclable cold storage phase change composite material is reduced.
[0074] In a preferred embodiment of the present invention, the polymer aerogel can be dissolved in ammonia water at 0-150° C. to form a solution containing the polymer. Preferably, the solution containing the polymer can be recovered to obtain the polymer aerogel by pre-freezing, freeze-drying, and heat treatment.
[0075] In a preferred embodiment of the present invention, the thermal conductivity of the polymer aerogel is less than 0.05 W / (m·K), preferably less than 0.04 W / (m·K). The polymer aerogel of the present invention has low thermal conductivity and can be used directly as a thermal insulation material without any treatment.
[0076] In a preferred embodiment of the present invention, the density of the polymer aerogel is 100 kg / m 3 Below, preferably 10-100kg / m 3 , preferably 15-80kg / m 3 Specifically, for example, 15 kg / m 3 、35kg / m 3 , 45kg / m 3 , 55kg / m 3、65kg / m 3 , 75kg / m 3 、80kg / m 3 , and any two values or any interval between any two values; and / or the polymer aerogel is a porous material. The polymer aerogel of the present invention has high porosity and is a porous material that can be used as a carrier. For example, it can be used as a skeleton to support an organic phase change material, thereby preventing leakage of the phase change material. The prepared phase change composite material can also be recovered using ammonia water.
[0077] In a preferred embodiment of the present invention, based on the total molar amount of the structural units containing maleic anhydride groups and the structural units containing maleimide groups as 100%, the molar ratio of the structural units containing maleimide groups in the polymer is 5%-70%, preferably 10%-60%; more preferably 20%-50%, for example, 20%, 25%, 30%, 35%, 40%, 45%, 50%, and any two values or any interval between any two values.
[0078] According to the present invention, the polymer can be selected from a wide range. In a preferred embodiment of the present invention, the polymer is derived from one or more polymer raw materials containing structural units containing maleic anhydride, maleimide, maleic acid and ammonium salt, maleamic acid and ammonium salt groups.
[0079] The maleic anhydride group refers to The maleimide group refers to Maleic acid and ammonium salt groups, maleamic acid and ammonium salt groups refer to Wherein M is the same or different and each is hydroxyl, amino or ammonium (-ONH4).
[0080] According to the invention, the polymers are carbon chain polymers in which the heteroatoms O and N are present in side groups.
[0081] Preferably, the polymer raw material is a copolymer of one or more polymer monomers selected from maleic anhydride, maleimide, maleic acid and ammonium salt, maleamic acid and ammonium salt, and an olefin monomer; more preferably, the olefin monomer is at least one of α-methylstyrene, styrene, and isobutylene.
[0082] In a preferred embodiment of the present invention, the polymer aerogel can be dissolved in ammonia water at 0-150°C to form a polymer-containing solution. Preferably, the polymer-containing solution can be recovered by pre-freezing, freeze-drying, and heat-treating to obtain the polymer aerogel. Therefore, the polymer aerogel of the present invention can be conveniently and environmentally friendly recycled.
[0083] In a preferred embodiment of the present invention, the polymer aerogel has photoluminescence properties and can change light signals as temperature changes. The photoluminescence properties of the polymer aerogel in the present invention can also be used as an indicator material to show temperature changes.
[0084] In a preferred embodiment of the present invention, the polymer aerogel has a static water contact angle of 100° or greater, preferably 110° or greater, and more preferably 135° or greater. In a preferred embodiment of the present invention, the polymer aerogel is insoluble in water and preferably does not dissolve to form an aqueous polymer solution after immersion in water at 20-40°C for 24 hours, preferably 72 hours, and more preferably 168 hours. The polymer aerogel of the present invention exhibits both superlipophilicity and hydrophobicity and can be used directly as an oil-water separation material without any further treatment.
[0085] In a preferred embodiment of the present invention, the method for preparing the polymer aerogel comprises reacting a polymer raw material containing one or more structural units selected from the group consisting of maleic anhydride, maleimide, maleic acid and ammonium salt, and maleamic acid and ammonium salt with aqueous ammonia under closed conditions, followed by pre-freezing, freeze-drying, and heat treatment for dehydration and deamination to obtain the polymer aerogel.
[0086] The aerogel preparation method of the present invention only requires heat treatment of the water-soluble aerogel, avoiding the need for introducing a crosslinking agent or performing a hydrophobic treatment to produce a hydrophobic and water-resistant aerogel. The preparation method is simple, easy, and environmentally friendly, and is applicable to the preparation of various maleimide copolymer aerogels. No crosslinking agent is added in the aerogel preparation method of the present invention.
[0087] The seventh aspect of the present invention is to provide a method for preparing the recyclable cold storage phase change composite material described in the sixth aspect, comprising loading the phase change material in the polymer aerogel; preferably, first preparing the polymer aerogel, and then loading the phase change material in the polymer aerogel.
[0088] The method for loading the phase change material into the polymer aerogel may be any of the various loading methods known in the art. Specifically, the phase change material may be loaded by filling or injecting the phase change material into the composite aerogel while the phase change material is in a liquid state, so that the phase change material is adsorbed and / or permeated into the composite aerogel.
[0089] The preparation method of the polymer aerogel includes reacting a polymer raw material containing one or more structural units selected from the group consisting of maleic anhydride, maleimide, maleic acid and ammonium salt, and maleamic acid and ammonium salt with aqueous ammonia under closed conditions, followed by pre-freezing, freeze-drying, and heat treatment for dehydration and deamination to obtain the polymer aerogel.
[0090] The aerogel preparation method of the present invention only requires heat treatment of the water-soluble aerogel, avoiding the introduction of a crosslinking agent or hydrophobic treatment to prepare the hydrophobic and water-resistant aerogel. The preparation method is simple, easy, green and environmentally friendly, and is applicable to the preparation of various types of maleimide copolymer aerogels.
[0091] In a preferred embodiment of the present invention, the preparation method comprises the following steps: (1) reacting a polymer raw material containing one or more structural units selected from the group consisting of maleic anhydride, maleimide, maleic acid and ammonium salt, and maleamic acid and ammonium salt with aqueous ammonia under closed conditions to obtain a polymer aqueous solution; (2) pre-freezing the polymer aqueous solution obtained in step (1) and then freeze-drying it to obtain a water-soluble polymer (i.e., a polymer aerogel precursor); (3) heat-treating the water-soluble polymer obtained in step (2) to obtain the polymer aerogel; and (4) loading the phase change material into the polymer aerogel.
[0092] According to the present invention, the amount of polymer raw material and ammonia water in step (1) can be selected within a wide range. In a preferred embodiment of the present invention, in step (1):
[0093] Based on the total mass of the reaction system as 100%, the mass fraction of the polymer raw material used is 0.1%-30%, preferably 1%-10%, more preferably 2%-5%. Based on the mass of ammonia in ammonia water, the mass fraction of ammonia in the raw material is 0.001%-30%, preferably 0.01%-10%, more preferably 0.1%-1%. The remaining components are water.
[0094] According to the present invention, the reaction conditions in step (1) can be selected within a wide range. In a preferred embodiment of the present invention, the reaction conditions include: a reaction temperature of 0-200°C, preferably 50-150°C, more preferably 80-100°C, and / or a reaction time of 0.01-100h, preferably 0.5-10h, more preferably 1-5h.
[0095] In a preferred embodiment of the present invention, step (2) includes pre-freezing the polymer aqueous solution obtained in step (1) in a pre-freezing container to obtain ice cubes. The pre-freezing container can be of any shape and size and can be customized according to the required aerogel. Freezing can be performed using a cold source such as a refrigerator, or using liquid nitrogen or the like. In this step, if the cold source temperatures in all directions of the pre-freezing container are consistent, the prepared aerogel is isotropic; if the cold source temperatures in all directions of the pre-freezing container are different, anisotropic aerogel can be prepared. Preferably, different unidirectional cold source temperatures during pre-freezing can obtain anisotropic aerogels. There are many options for implementing the unidirectional cold source temperature, including but not limited to using liquid nitrogen as a low-temperature cold source during pre-freezing, placing the pre-freezing container on a copper column immersed in liquid nitrogen, and allowing ice crystals to grow upward from the bottom of the container.
[0096] Specifically, the pre-freezing conditions may be conventional temperature conditions in the art and are not particularly limited in the present invention, as long as the polymer aqueous solution is frozen into ice.
[0097] According to the present invention, the freeze-drying conditions can be selected within a wide range, and the present invention is not particularly limited. In a preferred embodiment of the present invention, the freeze-drying conditions include: a temperature of below -10°C, for example, below -20°C, or below -30°C. According to the present invention, the vacuum degree of freeze-drying can be selected within a wide range. In a preferred embodiment of the present invention, the vacuum degree is below 1000 Pa, for example, below 100 Pa, or below 10 Pa. The above freeze-drying conditions can be flexibly selected based on cost, efficiency, and the conventional operation mode of the equipment.
[0098] The freeze drying process can adopt various freeze drying equipment in the prior art, such as freeze dryer, freeze spray dryer, industrial freeze dryer, etc.
[0099] According to the present invention, the conditions for the heat treatment in step (3) can be selected within a wide range. In a preferred embodiment of the present invention, the conditions for the heat treatment in step (3) include:
[0100] The temperature is 100-300°C, preferably 130-200°C, more preferably 150-190°C, and / or the time is 0.1-10 hours, preferably 0.5-3 hours, more preferably 1-2 hours. The reaction pressure is not particularly limited, but is preferably carried out under normal pressure.
[0101] According to the present invention, the polymer raw material can be selected from a wide range. In a preferred embodiment of the present invention, the polymer raw material is a polymer containing one or more structural units containing maleic anhydride, maleimide, maleic acid and ammonium salt, maleamic acid and ammonium salt groups; preferably, the polymer raw material is a copolymer of one or more polymerization monomers including maleic anhydride, maleimide, maleic acid and ammonium salt, maleamic acid and ammonium salt and an olefin monomer; more preferably, the olefin monomer includes at least one of α-methylstyrene, styrene, isobutylene, and vinyl acetate.
[0102] For example, the polymer raw material includes but is not limited to at least one of styrene maleic anhydride copolymer, methylstyrene maleic anhydride copolymer, and maleic anhydride isobutylene copolymer.
[0103] The polymer raw materials mentioned above are all polymers disclosed in the prior art, and can be commercially available from the prior art, or prepared according to the methods disclosed in the prior art.
[0104] In the present invention, there is no particular limitation on the material of the sealed container, which may be made of metal, non-metal, polymer or other materials.
[0105] More specifically, the preparation process of the polymer aerogel of the present invention includes the following steps: a. reacting a polymer raw material containing one or more structural units selected from the group consisting of maleic anhydride, maleimide, maleic acid and ammonium salt, or maleamic acid and ammonium salt with ammonia water in a sealed container and heating the reaction to prepare a polymer aqueous solution; b. pouring the polymer aqueous solution into a pre-freezing container, pre-freezing the container until it is completely frozen into ice cubes, and then freeze-drying the container in a freeze dryer for a predetermined period of time to obtain a water-soluble polymer; and c. heat-treating the water-soluble polymer under constant temperature conditions to dehydrate and deaminate the polymer to obtain a water-resistant maleimide-based aerogel.
[0106] During pre-freezing, the temperature of the cold source in each direction of the solution is the same or different. More preferably, the temperature of the cold source in each direction of the solution is different during pre-freezing to obtain anisotropic aerogel; most preferably, the temperature of the cold source in one direction of the pre-freezing solution is different to obtain anisotropic aerogel.
[0107] In a preferred embodiment of the present invention, in the pre-freezing stage, the cooling source temperatures of the polymer aqueous solution obtained in step (1) are different in all directions, preferably different in one direction.
[0108] In a more preferred embodiment of the present invention, before pre-freezing in step (2), a mold is inserted into the polymer aqueous solution obtained in step (1). The mold can be inserted to the bottom and contact the bottom of the pre-freezing container, or it can be separated from the bottom of the pre-freezing container, with the latter being preferred. After the heat treatment in step (3), the mold is optionally removed to obtain a polymer aerogel having a cavity, and the phase change material is filled into the polymer aerogel in step (4). In this way, the pre-stored material can be placed in the cavity left after the mold is removed, which facilitates storage.
[0109] The mold of the present invention, if provided with a cavity structure, can be left in place, and pre-stored items can be placed in the mold cavity during use. Simultaneously, refrigerated items (such as vaccines and medicines) can be placed in the cavity, creating a more uniform cold storage environment for the refrigerated items and achieving better preservation.
[0110] The present invention has no particular restrictions on the selection of the mold, and the material can be glass, plastic, metal, etc.; the mold can be solid or have a cavity structure, and its shape is not limited, preferably cylindrical, columnar, etc.; as for the structure of the mold, when it is taken out, it can be solid or have a cavity structure; when it is not taken out, the mold preferably has a cavity structure with an opening at the top; as for the size of the mold, it can be adjusted according to the size of the pre-stored object, and the present invention has no particular restrictions.
[0111] The “and / or” involved in the present invention means that the two conditions before and after “and / or” can be selected one by one, or the two conditions can exist at the same time.
[0112] Real-time temperature monitoring of phase change materials is also crucial. For example, most vaccines, including the COVID-19 vaccine, must be kept below 8°C during transportation and storage. Therefore, real-time temperature monitoring is necessary for each vaccine. Organic phase change materials also need to be reprocessable and recyclable to avoid environmental pollution and resource waste.
[0113] Based on the above technical problems, the eighth aspect of the present invention is to provide a recyclable cold storage phase change material with real-time temperature monitoring function. The recyclable cold storage phase change material has a layer structure, including an inner layer formed by the recyclable cold storage phase change composite material described in the sixth aspect or the recyclable cold storage phase change composite material prepared by the preparation method described in the seventh aspect, and an outer layer formed by a second polymer aerogel.
[0114] According to the present invention, the thickness of the inner layer and the thickness of the outer layer can be selected within a wide range. In a preferred embodiment of the present invention, the thickness of the inner layer is greater than 3 mm, and the thickness of the outer layer is greater than 5 mm.
[0115] In a preferred embodiment of the present invention, a spacer layer is further provided between the inner layer and the outer layer. The present invention has no particular limitations on the material of the spacer layer, as long as it can separate the aerogel encapsulating the phase change material internally from the insulating aerogel externally, preventing interpenetration. Materials include, but are not limited to, metals (e.g., thin aluminum foil) and plastics.
[0116] The thickness of the inner layer can be controlled during the manufacturing process according to the distance between the four walls of the mold or the four walls and the bottom and the spacer layer. The thickness of the outer layer can be controlled according to the distance between the four sides of the spacer layer and the outer container wall.
[0117] The above recyclable cold storage phase change material can be cylindrical with a radial layer structure, with the outer layer being the second polymer aerogel and the inner layer being the recyclable cold storage phase change composite material, with a spacer layer provided between the two layers; or the above recyclable cold storage phase change material can be flat with a layer structure, with a spacer layer in the middle, with one side of the spacer layer being the outer layer of the second polymer aerogel and the other side being the inner layer of the recyclable cold storage phase change composite material; preferably, the outermost surface of the recyclable cold storage phase change material is also wrapped with a packaging material. The present invention has no particular restrictions on the shape and structure of the spacer layer, for example, it can be cylindrical or flat, as long as it can be coated on the outside of the inner aerogel layer to isolate the inner and outer layers.
[0118] Preferably, the inner layer is provided with a cavity; the cavity is formed from the mold itself or after the mold is removed. In applications, refrigerated items (such as vaccines, medicines, etc.) can also be placed in the cavity, making the cold storage environment in which the refrigerated items are located more uniform and improving the preservation effect.
[0119] According to the present invention, the second polymer aerogel can be selected from a wide range. Preferably, the second polymer aerogel has photoluminescence (i.e., fluorescence) properties, and the optical signal can change with temperature. The optical signal here refers to the peak position and / or intensity of the fluorescence spectrum.
[0120] In a preferred embodiment of the present invention, the second polymer aerogel is selected from at least one polymer aerogel having photoluminescence properties (i.e., fluorescence properties) and capable of changing light signals with changes in temperature in the recyclable cold storage phase change composite material according to the sixth aspect; and the second polymer aerogel may be the same as or different from the polymer aerogel in the recyclable cold storage phase change composite material. More preferably, the second polymer is a styrene maleic anhydride maleimide copolymer aerogel (i.e., a copolymer formed by a polymer monomer comprising one or more of maleic anhydride, maleimide, maleic acid and ammonium salt, or maleamic acid and ammonium salt, and styrene). The inventors of the present invention have discovered that the styrene maleic anhydride maleimide copolymer aerogel has fluorescence properties capable of changing light signals with changes in temperature.
[0121] As an example, in a specific embodiment of the present invention, the phase change cold storage material described in the present invention is characterized in that the inner layer is the aerogel phase change composite material described in the sixth aspect, and the outer layer is the polymer aerogel used in the aerogel phase change composite material described in the sixth aspect. Preferably, the aerogel has a photoluminescence effect (for example, it can be a styrene maleic anhydride / maleimide copolymer aerogel), and the intensity changes with temperature (for example, it increases with decreasing temperature). Therefore, the temperature of the phase change material can be determined by measuring the fluorescence intensity, thereby realizing real-time temperature monitoring of the cold storage material.
[0122] A ninth aspect of the present invention provides a method for preparing the recyclable cold storage phase change material with real-time temperature monitoring function according to the eighth aspect, characterized in that it comprises the following steps:
[0123] (1) reacting a polymer raw material containing one or more structural units selected from the group consisting of maleic anhydride, maleimide, maleic acid and ammonium salt, and maleamic acid and ammonium salt with aqueous ammonia in a sealed environment to obtain a polymer aqueous solution;
[0124] (2) placing a polymer aqueous solution in the space inside the spacer layer or in the space between the inner side of the spacer layer and the mold, and then pre-freezing and freeze-drying to obtain a water-soluble polymer (i.e., a polymer aerogel precursor);
[0125] (3) heat-treating the water-soluble polymer obtained in step (2), and optionally removing the mold to obtain a polymer aerogel having a cavity;
[0126] (4) filling the polymer aerogel obtained in step (3) with a phase change material to form an inner layer of the recyclable cold storage phase change material;
[0127] wherein, in step (2), step (3), step (4) and / or between steps and / or after step (4), the second polymer aerogel is coated on the outside of the spacer layer, thereby forming the outer layer of the recyclable cold storage phase change material;
[0128] or,
[0129] In step (2), an aqueous solution containing a second polymer aerogel and / or a second polymer aqueous solution is placed in the space outside the spacer layer to form an outer layer of the recyclable cold storage phase change material; preferably, the second polymer aqueous solution is the same as the polymer aqueous solution in step (1);
[0130] That is, step (2) is preferably performed in the following manner:
[0131] The polymer aqueous solution is placed in the outer space of the spacer layer, the inner space of the spacer layer or the space between the inner side of the spacer layer and the mold to obtain a water-soluble polymer with a layer structure.
[0132] According to the above technical solution, the method for preparing a recyclable cold storage phase change material with real-time temperature monitoring functionality includes a polymer aerogel preparation process. The polymer aerogel located within the spacer layer can be prepared using the aforementioned method for preparing the polymer aerogel (recyclable polymer aerogel). Simultaneously, during the preparation of the inner polymer aerogel, a second polymer aerogel, or an aqueous solution containing the second polymer aerogel, and / or a second polymer aqueous solution is coated on the outside of the spacer layer. The timing of coating the second polymer aerogel, or an aqueous solution containing the second polymer aerogel, and / or the second polymer aqueous solution on the outside of the spacer layer can be determined based on the type of second polymer aerogel selected. For example, when the second polymer aerogel is the polymer aerogel described above (i.e., the same type as the polymer aerogel in the inner layer), the water-soluble polymer in step (1) can be arranged outside the spacer layer in step (2), and then subsequent processing steps can be performed. In this way, after the processing step of step (3), both the inside and outside of the spacer layer are recyclable polymer aerogels; if the second polymer aerogel (or precursor) does not need to be freeze-dried but needs heat treatment, the second polymer aerogel (or precursor) can also be arranged outside the spacer layer in step (2); when the second polymer aerogel (or precursor) does not need to be heat treated, the second polymer aerogel product can also be arranged outside the spacer layer in step (3) or step (4) or after step (4). In short, based on the principle of procedure or process saving, it can be flexibly adjusted according to the type of the second polymer aerogel.
[0133] Specifically, the amount of aerogel raw material in the inner layer and the outer layer can be selected within a wide range. Preferably, the amount is such that the thickness of the inner layer in the finished product is greater than 3 mm, and the thickness of the outer layer is greater than 5 mm.
[0134] Regarding the selection of the second polymer aerogel or (precursor), the selection of the phase change material, the amount of use, etc., the selection of the second polymer aerogel or (precursor), the selection of the phase change material, and the amount of use described in the eighth aspect can be adopted, and no further details will be given here.
[0135] In a preferred embodiment of the present invention, the mass fraction of the polymer content in the polymer aqueous solution of the inner layer is 0.1%-30%, preferably 1%-10%, more preferably 2%-5%, and / or the mass fraction of the second polymer content in the aqueous solution of the second polymer aerogel and / or the second polymer aqueous solution is each 0.1%-30%, preferably 0.5%-10%, more preferably 1%-5%.
[0136] In a preferred embodiment of the present invention, in step (2), during the pre-freezing stage, the cooling source temperature of the polymer aqueous solution obtained in step (1) is different in all directions, preferably in one direction. In this way, an anisotropic aerogel can be obtained. In this preferred embodiment, the leakage rate of the obtained cold storage material is lower.
[0137] The pre-freezing container can be of any shape and size, customizable to the desired aerogel or refrigerated item. Freezing can be performed using a cold source such as a refrigerator or liquid nitrogen. If the cold source temperature in all directions of the mold is consistent, the resulting aerogel will be isotropic. If the cold source temperature in all directions of the pre-freezing container varies, anisotropic aerogels can be produced. Anisotropic aerogels are preferred, and anisotropic aerogels with varying cold source temperatures in a single direction are more preferred.
[0138] The specific conditions in the above steps (1), (2) and (3) can be selected within a wide range, and preferably, the preferred conditions in the above-mentioned method for preparing polymer aerogel can be adopted.
[0139] More specifically, the heat treatment temperature in step (3) is 100-300°C, preferably 120-220°C, more preferably 160-200°C; the heat treatment time is 0.1-10 hours, preferably 0.5-3 hours, more preferably 1-2 hours.
[0140] According to the present invention, the method for recovering the recyclable polymer aerogel in the recyclable cold storage phase change composite material mentioned above can adopt the following method:
[0141] The recovery method comprises mixing the polymer aerogel and / or a material containing the polymer aerogel with aqueous ammonia under closed conditions until an aqueous solution containing the recovered polymer is obtained, and optionally removing insoluble matter to obtain an aqueous solution of the recovered polymer. This aerogel recovery method does not require the introduction of organic solvents or high-temperature, high-pressure stirring. It only requires a certain concentration of aqueous ammonia, preferably maintained below 100 degrees Celsius, enabling rapid and efficient recovery. This method has low energy consumption, minimal pollution, and high efficiency. The recovered polymer solution can be reused in the preparation of polymer aerogels.
[0142] The polymer aerogel recovery method of the present invention comprises placing the polymer aerogel in ammonia water of a certain concentration, placing the polymer aerogel in a sealed container, heating the aerogel at a certain temperature, and waiting for the aerogel to be completely dissolved to obtain a copolymer aqueous solution.
[0143] According to the present invention, the conditions for the mixed reaction in the recovery method can be selected within a wide range. In a preferred embodiment of the present invention, the temperature of the mixed reaction is 0-200°C, preferably 50-150°C, more preferably 80-100°C, and / or the time of the mixed reaction is 0.01-100h, preferably 0.5-10h, more preferably 1-5h.
[0144] In a preferred embodiment of the present invention, the recovery method further comprises freeze-drying and heat-treating the aqueous solution of the recovered polymer to recover the polymer aerogel; preferably, the freeze-drying conditions include: a temperature below -10°C, which may be below -20°C, or below -30°C, and / or a vacuum degree below 1000 Pa, which may be below 100 Pa, or below 10 Pa.
[0145] According to the present invention, the conditions for heat treatment can be selected within a wide range. In a preferred embodiment of the present invention, the conditions for heat treatment include:
[0146] The temperature is 100-300° C., preferably 130-200° C., more preferably 150-190° C. and / or the time is 0.1-10 h, preferably 0.5-3 h, more preferably 1-2 h.
[0147] When it comes to the recovery of the recyclable cold storage phase change composite material and the recyclable polymer aerogel in the recyclable cold storage phase change material with real-time temperature monitoring function in the present invention, the above-mentioned method can be used to treat the recyclable cold storage phase change composite material or the recyclable cold storage phase change composite material of the inner layer in the recyclable cold storage phase change material with real-time temperature monitoring function in ammonia water, separate the polymer from the phase change material, and then undergo a post-processing step to obtain the recyclable polymer aerogel, or the preparation method of the recyclable cold storage phase change composite material or the recyclable cold storage phase change material with real-time temperature monitoring function is used again to obtain the recyclable cold storage phase change composite material or the recyclable cold storage phase change material with real-time temperature monitoring function in the present invention.
[0148] When the second polymer aerogel is the recyclable polymer aerogel of the present invention (the polymer in the polymer aerogel contains maleic anhydride groups and maleimide groups), the above method can be used to recycle it together with the inner layer material. When the second polymer aerogel is a different type of polymer aerogel, the second polymer aerogel of the outer layer of the recyclable cold storage phase change material with real-time temperature monitoring function can be peeled off and then the subsequent recovery steps can be carried out.
[0149] The tenth aspect of the present invention is to provide a recyclable cold storage phase change composite material as described in the sixth aspect or the recyclable cold storage phase change composite material prepared by the preparation method as described in the seventh aspect, the recyclable cold storage phase change material with real-time temperature monitoring function as described in the eighth aspect or the recyclable cold storage phase change material with real-time temperature monitoring function prepared by the preparation method as described in the ninth aspect, and their application in the fields of food preservation and cold chain transportation.
[0150] According to the above technical solution, the present invention provides a recyclable polymer aerogel, its preparation method, recycling method, and application. The present invention also provides a recyclable cold storage phase change composite material, a recyclable aerogel phase change cold storage material with real-time temperature monitoring function, its preparation method, and application. Compared with the existing technology, the present invention has the following advantages:
[0151] The polymer aerogel of the present invention does not require cross-linking or hydrophobicization treatment, and has characteristics such as super oleophilicity and hydrophobicity. It does not require any treatment and can be directly used as an oil-water separation material. The polymer aerogel of the present invention can also be conveniently and environmentally friendly for recycling, with a recycling efficiency of more than 99%. The aerogel preparation and recycling process does not require the use of any organic solvents, and has the characteristics of low energy, high efficiency, and environmental protection. In addition, the polymer aerogel of the present invention has low thermal conductivity, low density, and good heat resistance, and can be used in a variety of fields, with extremely high application value. The present invention is the first to prepare aerogels from maleimide-based polymers, broadening the application range of copolymers containing maleic anhydride and maleimide groups.
[0152] The recyclable cold storage phase change composite material in the present invention includes a polymer aerogel and a phase change material loaded in the polymer aerogel; wherein the polymer in the polymer aerogel contains a structural unit containing a maleic anhydride group and a structural unit containing a maleimide group. The polymer aerogel can be recovered in ammonia water, and the recovered polymer aerogel obtained through post-treatment (including heat treatment) can be reused again. Based on this, the recyclable cold storage phase change composite material in the present invention can be recycled repeatedly. The recyclable cold storage phase change composite material in the present invention is not only recyclable, but also has strong cold storage performance, and the leakage of the phase change material is less, and it can maintain a low temperature for a long time. It can be widely used in food preservation, cold chain transportation (such as cold chain transportation of vaccines and medicines), and other links.
[0153] Moreover, the recyclable cold storage phase change material with real-time temperature monitoring function in the present invention has a sandwich structure, including an inner layer formed by a recyclable cold storage phase change composite material and an outer layer formed by a second polymer aerogel, which can achieve better thermal insulation performance. When the preferred second polymer aerogel has photoluminescent properties and can change the light signal as the temperature changes, temperature monitoring can be better achieved, thereby achieving large-scale temperature monitoring and recyclable performance at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0154] FIG1 is a Fourier transform infrared spectrum test curve of comparative example 3A, example 1A, and the aerogel recovered from example 1A;
[0155] FIG2 is a hydrogen nuclear magnetic resonance spectrum curve of Example 1A and the aerogel recovered from Example 1A;
[0156] As shown in Figures 1 and 2, in the Fourier infrared spectrum (Figure 1), 3207 cm -1 and 3444cm -1 There are obvious NH stretching vibration absorption peaks and hydrogen bond characteristic absorption peaks at 1780 cm -1 and 1857cm -1 The peaks at 1716 cm are the asymmetric stretching vibration and symmetric stretching vibration of C=O in maleic anhydride. -1 and 1662cm -1 The absorption peaks at 935 cm indicate the presence of carboxyl and amide groups. -1 The absorption peak at 1349 cm is the characteristic absorption peak of COC in the five-membered ring of acid anhydride, and the absorption peak at 1349 cm is the characteristic absorption peak of COC in the five-membered ring of acid anhydride. -1 The absorption peak at [Number] belongs to the CN stretching vibration peak unique to the imide ring. In the H NMR spectrum (Figure 2), the chemical shifts of the five hydrogen atoms on the benzene ring range from 7.7 to 6.0 ppm, while the chemical shifts of the hydrogen atoms on the NH group of maleimide range from 10.2 to 9.4 ppm. Using the hydrogen atoms on the benzene ring as the internal standard, the ratio of maleimide to maleic anhydride (maleic anhydride in the polymer feedstock is equal to the total amount of maleic anhydride + maleimide in the polymer aerogel) (i.e., the maleimidation rate) can be calculated by integrating the areas of maleimide and benzene ring hydrogen atoms. In summary, the aerogel infrared spectrum curve in Figure 1 and the aerogel H NMR spectrum curve in Figure 2 confirm the presence of maleimide structures in the aerogel structure.
[0157] FIG3 is a scanning electron microscope photograph of the pore structure of the aerogel obtained in Example 1A, which proves the existence of the porous structure of the aerogel.
[0158] FIG4 is a temperature rise curve of the cold storage phase change material obtained in Example 1B;
[0159] The test results in Figure 4 show that the prepared phase change material can maintain low temperature for a long time;
[0160] FIG5 is an emission spectrum of the maleimide-based aerogel in the outer layer of the phase-change cold storage material prepared in Example 1B at an excitation wavelength of 400 nm.
[0161] Figure 5 shows that the temperature of the phase change material can be monitored in real time through the fluorescence-temperature relationship of the surface aerogel.
[0162] Figure 6 is a schematic diagram showing the appearance of the recyclable cold storage phase change composite material (a), the recovered phase change material (b), and the recovered polymer aerogel (c) in Recycling Example B. It can be seen that the recyclable cold storage phase change composite material in the present invention can be recycled;
[0163] FIG7 is a schematic diagram of the three-dimensional structure of the aerogel phase change cold storage material with real-time temperature monitoring function obtained in Example 1B;
[0164] FIG8 is a schematic diagram of the longitudinal cross-sectional structure of the aerogel phase change cold storage material with real-time temperature monitoring function obtained in Example 1B.
[0165] Among them, 1 is the outer layer; 2 is the spacer layer; 3 is the inner layer; 4 is the cavity. DETAILED DESCRIPTION
[0166] The present invention will be described in detail below with reference to specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and are not to be construed as limiting the scope of protection of the present invention. Non-essential improvements and adjustments made by those skilled in the art to the present invention based on the contents of the present invention still fall within the scope of protection of the present invention.
[0167] The experimental data in the examples were measured using the following instruments and measurement methods:
[0168] 1. Measurement method of water solubility of aerogel:
[0169] Take 1g of aerogel and place it in 100g of water at room temperature. After soaking for 72 hours, remove it and dry it. The mass m1 is measured. When m1 is greater than 99%, the polymer aerogel is considered water-resistant. When the aerogel completely dissolves in water, it is considered water-soluble.
[0170] 2. Measurement method of water contact angle of aerogel:
[0171] The water contact angle of the product obtained in the embodiment was measured using a German EASYDROP contact angle tester: the polymer aerogel was cut into pieces of about 10*10*2mm with a thin blade. 3The aerogel sheet was fixed on the operating table. During the fixing process, the sample was kept flat in the horizontal direction. Then the slide was placed on the sample stage of the EASYDROP contact angle meter and fixed. The instrument was adjusted to control the volume to 4±0.02μL and a water droplet was dropped into the center of the sample. After the water droplet was dropped on the aerogel surface for 1 minute, the angle from the solid-liquid interface through the inside of the droplet to the vapor-liquid interface at the junction of the three phases was measured, which is the water static contact angle (abbreviated as water contact angle).
[0172] 3. Measurement method of thermal conductivity of aerogel:
[0173] A TC3100 hot wire universal thermal conductivity meter produced by Xi'an Xiaxi Electronic Technology Co., Ltd. was used. First, the aerogel was cut into pieces of about 30*20*5mm with a thin blade. 3 A thin sheet is formed, and two aerogel sheets are used to cover both sides of the test probe. After pressing with weights, the test temperature is adjusted to 25 degrees Celsius, and the test method is set to the insulation material sample test. The thermal conductivity coefficient obtained from the test results is the average value of at least 5 measurement results.
[0174] 4. Fourier transform infrared spectroscopy characterization method of aerogel structure:
[0175] The aerogels in the examples were tested using a Nicolet IS5 Fourier transform infrared spectrometer from the United States. The infrared spectra of the samples were collected by KBr pelleting. An appropriate amount of aerogel was ground with KBr and pelleted. The scan count was set to 32, the spectrum was collected in the range of 400-4000 cm, and the optical frequency was 1 cm. -1 .
[0176] 5. Structural characterization of aerogels by hydrogen nuclear magnetic resonance spectrum:
[0177] The aerogel samples in the examples were analyzed using an Agilent 400-MR DD2 nuclear magnetic resonance spectrometer. 1 H NMR test. Dimethyl sulfoxide-d6 was used as the solvent for water-soluble aerogels, while acetone-d6 was used as the solvent for hydrophobic and water-resistant aerogels, and tetramethylsilane (TMS) was used as the internal reference reagent.
[0178] 6. Aerogel pore structure test method:
[0179] The pore structure of the aerogel samples in the examples was observed using an EM30AX scanning electron microscope (SEM) from COXEM, South Korea. The sample to be tested was first coated with gold. The coated sample was then placed on the SEM inspection platform and scanned with the microscope to obtain a photograph of the pore structure.
[0180] 7. Thermal stability test method of aerogel:
[0181] The thermal stability of the samples was determined by thermogravimetric analysis (TGA, Mettler Toledo, Switzerland). 5 mg of aerogel was tested under a nitrogen flow at a heating rate of 20°C / min from 50°C to 550°C.
[0182] 8. Glass transition temperature test method:
[0183] The glass transition temperature of the samples was measured using a Perkin-Elmer pyris -1 Differential scanning calorimetry (DSC) was performed using indium and zinc standards for calibration. A 5-6 mg sample was injected from a rod and heated from 150°C to 300°C under a nitrogen stream, held at 300°C for 3 minutes. The sample was then cooled to 150°C for 1 minute and then heated again to 300°C. All heating and cooling processes were programmed at a rate of 10°C / min. The glass transition temperature (Tg) was determined from the relevant peaks in the DSC curve.
[0184] 9. Leakage test method:
[0185] Take 15g of the sample obtained in Example 1, place filter paper on a 30°C hot plate, and invert the sample onto the filter paper for 10 minutes. Remove the sample and weigh it to obtain m (g). The leakage rate is: m / 15 * 100 wt%. If the sample is completely melted and cannot be removed, the leakage rate is 100 wt%.
[0186] 10. Three-dimensional fluorescence spectrum test method:
[0187] The fluorescence spectrum of the nano fluorescent elastic particles was tested using an F-7000 FL Spectrophotometer. The test method was Wavelength Scan, with the excitation wavelength set at 400 nm to measure the emission spectrum.
[0188] 11. Test method for cold storage capacity of phase change materials:
[0189] 10 mL of ethanol was added to a 10 mL glass vial and frozen to -30°C. The vial was then placed in a 25°C incubator. A thermocouple was inserted into the ethanol to evaluate the cooling effect.
[0190] 12. Test method for adsorption capacity of phase change materials:
[0191] Use a balance to weigh the entire sample before the test as m1. After the phase change material is adsorbed and the excess phase change material on the surface is wiped off, the entire sample is weighed as m2. The amount of phase change material adsorbed is: m2-m1.
[0192] 13. Phase change temperature test method:
[0193] The thermal properties of aerogels and phase-change materials were measured using differential scanning calorimetry (DSC) using a Perkin-Elmer pyris-1 calibrated with indium and zinc standards. For aerogels, samples were heated from 20°C to 150°C under a nitrogen flow, holding at 20°C and 150°C for 5 min each. For phase-change materials, samples were heated from 50°C to 300°C under a nitrogen flow, holding at 50°C and 300°C for 5 min each. All heating and cooling processes were programmed at a rate of 20°C / min. The latent heats of melting, ΔHm, and solidification, ΔHf, as well as the melting and solidification temperatures, Tm and Tf, were determined from the relevant peaks in the DSC curves.
[0194] The raw materials used in the examples are described in Table 1.
[0195] Table I
[0196] Preparation Example 1A
[0197] Place 500 ml of isoamyl acetate in a 1000 ml three-necked flask and introduce nitrogen for 30 minutes to remove oxygen. Then, add 24.5 g of maleic anhydride and 26 g of styrene. Once completely dissolved, add 0.4 g of azobisisobutyronitrile. Heat the water bath to 70°C and allow to react for 7 hours. Centrifuge at 10,000 rpm for 10 minutes, remove the supernatant, add 500 ml of methanol, stir for 0.5 hours, centrifuge, and remove the supernatant. Repeat this process twice, then dry under vacuum at 140°C for 24 hours to obtain a styrene-maleic anhydride copolymer.
[0198] Preparation Example 2A
[0199] Place 500ml of isoamyl acetate in a 1000ml three-necked flask and introduce nitrogen for 30 minutes to remove oxygen. Add 24.5g of maleic anhydride and 26.2g of styrene to the flask, and then dropwise add 3.69g of Dayi DY-V421 vinyl silicone oil. Once completely dissolved, add 0.4g of azobisisobutyronitrile. Heat the water bath to 70°C and let react for 7 hours. Centrifuge at 10,000r / min for 10 minutes, remove the supernatant, add 500ml of methanol, stir for 0.5 hours, centrifuge, and remove the supernatant. Repeat this process twice, then dry under vacuum at 140°C for 24 hours to obtain a styrene-maleic anhydride-vinyl silicone oil copolymer.
[0200] Preparation Example 3A
[0201] Take the styrene-maleic anhydride copolymer in Preparation Example 1A, add 91.5 g of water to a covered glass bottle, then add 3.5 g of 25% ammonia water and 5 g of the above-mentioned maleic anhydride-styrene copolymer. After tightening the cap of the glass bottle, place it in an oven and maintain it at 95°C. After 4 hours, take it out to obtain a uniform 5% mass fraction polymer solution, and dry it at room temperature to obtain a polymer containing maleamic acid and ammonium maleate groups.
[0202] Example 1A
[0203] Take a glass bottle with a lid, add 91.5g of water, then add 3.5g of 25% ammonia water and 5g of maleic anhydride-styrene copolymer, tighten the lid of the glass bottle and place it in an oven maintained at 95°C. After 4 hours, take it out to obtain a uniform 5% mass fraction polymer solution.
[0204] The polymer solution was poured into 6 molds, with 15 ml of the solution poured into each mold. The molds were placed in a -30°C refrigerator and frozen for 2 hours. The frozen samples were transferred to a freeze dryer and freeze-dried (below -30°C, below 10 Pa) for 72 hours. The resulting water-soluble polymer was then taken out.
[0205] The water-soluble polymer is placed in a constant temperature container and heat treated at 180° C. for 2 hours to obtain a maleimide-based aerogel (ie, the polymer aerogel in the present invention) through dehydration and deamination.
[0206] Comparative Example 1A
[0207] The 91.5 g of water and 3.5 g of 25% ammonia water in Example 1A were replaced with 94 g of water and 1 g of sodium hydroxide. The other preparation steps were the same as those in Example 1A.
[0208] Comparative Example 2A
[0209] The 91.5 g of water and 3.5 g of 25% ammonia water in Example 1A were replaced with 94 g of water and 2 g of sodium hydroxide. The other preparation steps were the same as those in Example 1A.
[0210] Comparative Example 3A
[0211] The heat treatment process in Example 1A was not performed, and the other preparation steps were the same as in Example 1A.
[0212] Comparative Example 4A
[0213] The maleic anhydride in the maleic anhydride-styrene copolymer in Example 1A was replaced with nitrogen phenylmaleimide, and the other preparation steps were the same as in Example 1A.
[0214] Example 2A
[0215] The 91.5 g water, 3.5 g 25% ammonia water and 5 g maleic anhydride-styrene copolymer in Example 1A were replaced with 94.9 g water, 2.1 g 25% ammonia water and 3 g maleic anhydride-styrene copolymer. The other preparation steps were the same as in Example 1A.
[0216] Example 3A
[0217] The 91.5 g water, 3.5 g 25% ammonia water and 5 g maleic anhydride-styrene copolymer in Example 1A were replaced with 98.3 g water, 0.7 g 25% ammonia water and 1 g maleic anhydride-styrene copolymer. The other preparation steps were the same as in Example 1A.
[0218] Example 4A
[0219] The 5 g of maleic anhydride-styrene copolymer in Example 1A was replaced with 5 g of maleic anhydride-isobutylene copolymer (Kuraray ISOBAM-08). The other preparation steps were the same as those in Example 1A.
[0220] Example 5A
[0221] 5 g of the maleic anhydride-styrene copolymer in Example 1A was replaced with 5 g of the polymer obtained in Preparation Example 3A. The other preparation steps were the same as in Example 1A.
[0222] Example 6A
[0223] The maleic anhydride copolymer in Example 1A was replaced by the styrene maleic anhydride vinyl silicone oil copolymer in Preparation Example 2A, and the other preparation steps were the same as in Example 1A.
[0224] Example 7A
[0225] The method of Example 5A was followed, except that 3.5 g of 25% ammonia water was added instead of 3.5 g of water, the glass bottle was replaced with a reactor with a polytetrafluoroethylene liner, the oven temperature was changed from 95°C to 150°C, the oven holding time at 95°C was changed from 4 h to 12 h, a uniform 5% by mass polymer solution was obtained, the heat treatment temperature was changed to 130°C, and the remaining steps were the same as in Example 5A.
[0226] Example 8A
[0227] According to the method of Example 5A, the addition of 3.5 g of 25% ammonia water and 91.5 g of water was replaced by the addition of 40 g of 25% ammonia water and 55 g of water. The oven temperature in which the glass bottle was placed was changed from 95°C to 20°C, and the holding time was changed from 4 h to 0.5 h. The heat treatment temperature in Example 1A was changed to 200°C. The remaining steps were the same as in Example 5A.
[0228] Aerogel Cycle Efficiency Testing Method and Aerogel Recovery Method (Recovery Example A)
[0229] The water-resistant maleimide-based aerogel of the present invention is weighed to obtain a mass m1, which is added to 91.5g of water in a sealed glass bottle with a lid, followed by 3.5g of 25% ammonia water, and 5g (i.e., m1) of the water-resistant maleimide aerogel is added to the bottle. The sealed glass bottle with a lid is screwed on tightly and placed in an oven maintained at 95°C for 2 hours to obtain a uniform recovered polymer solution. The polymer solution is poured into 6 molds, with 15ml of the solution poured into each mold, and the molds are placed in a -30°C refrigerator for 2 hours. The frozen samples are transferred to a freeze dryer and freeze-dried for 72 hours, and the recovered water-soluble polymer is taken out. The recovered water-soluble polymer is placed in a constant temperature container and heat-treated at 180°C for 2 hours to dehydrate and deaminate to obtain a recovered water-resistant maleimide-based aerogel (i.e., the recovered polymer aerogel of the present invention).
[0230] The mass of the recovered water-resistant maleimide-based aerogel is m2, and the recovery efficiency is m2 / m1*100%.
[0231] Among them, the performance of the water-resistant maleimide-based aerogel (polymer aerogel) in Example 1A after one recovery is shown in Table 1A and Table 2A, and the corresponding sample name is Example 1A (Recovery 1). The recovered aerogel was recycled again, and the corresponding sample name was named Example 1A (Recovery 2).
[0232] It has been verified that the polymer aerogel (maleimide-based aerogel) in Example 1A of the present invention has good heat resistance, a glass transition temperature of around 250°C, and a decomposition temperature of around 300°C. The heat resistance of the aerogel prepared from the recycled polymer is higher than that before recycling, proving that the polymer has good heat resistance before and after aerogel recycling, and the recycling process is green and environmentally friendly.
[0233] Test Case
[0234] The water solubility test results of the aerogels prepared in Examples 1A-6A and Comparative Examples 1A-4A are listed in Table 1A, and the water contact angle, circulation efficiency, thermal conductivity, and density test results of the aerogels prepared in Examples 1A-8A are listed in Table 2A. Infrared spectra of Comparative Example 3A, Example 1A, and the aerogels recovered from Example 1A are shown in Figure 1. Nuclear magnetic resonance (NMR) tests of the Examples and Comparative Examples are shown in Figure 2. A scanning electron micrograph of the pore structure of the aerogel obtained in Example 1A is shown in Figure 3. The infrared spectra of the aerogels in Figure 1 and the proton nuclear magnetic resonance (HNMR) spectra of the aerogels in Figure 2 confirm the presence of maleimide structures in the polymer aerogel structure.
[0235] Table 1A
[0236] Table 2A Note: The maleimide ratio in Table 2A is the molar ratio of the structural units containing maleimide groups, based on the total molar amount of the structural units containing maleic anhydride groups and the structural units containing maleimide groups in the polymer aerogel being 100%.
[0237] Comparison of the test results of Examples 1A-6A and Comparative Examples 1A-4A in Table 1A shows that the aerogel prepared by the present invention is water-resistant and hydrophobic. Hydrophobic and water-resistant aerogels cannot be prepared using non-volatile bases such as sodium hydroxide. Ammonia cannot dissolve nitrogen phenylmaleimide, and similarly, it cannot be directly dissolved in ammonia to prepare hydrophobic aerogels.
[0238] It can be seen from the water contact angle, circulation efficiency, thermal conductivity and density test results of Examples 1A-6A in Table 2A that the thermal conductivity and density of aerogels are low, and they can directly replace existing low-density thermal insulation materials. Since the aerogel samples have extremely high circulation efficiency, they are more environmentally friendly. Its hydrophobicity is good and it can be used as an oil-water separation material. Due to its porous structure on the surface (Figure 3), the aerogel can be used as a carrier to load organic phase change materials, catalysts, etc., and can also be used as a filter material. After testing, the water contact angle, circulation efficiency, thermal conductivity and density test results of the polymer aerogels in Examples 7A and 8A are close to those in Example 5A.
[0239] Preparation Example 1B
[0240] In the present embodiment, the polymer was prepared by placing 500 ml of isoamyl acetate in a 1000 ml three-necked flask and purging it with nitrogen for 30 minutes to remove oxygen. Then, 24.5 g of maleic anhydride and 26 g of styrene were added to the flask. After complete dissolution, 0.4 g of azobisisobutyronitrile was added. The temperature in a water bath was raised to 70°C and the reaction was allowed to proceed for 7 hours. After the reaction, the mixture was centrifuged at 10,000 rpm for 10 minutes, the supernatant removed, and 500 ml of methanol added. The mixture was stirred for 0.5 hours, centrifuged, and the supernatant removed. This process was repeated twice, followed by vacuum drying at 140°C for 24 hours to obtain a styrene-maleic anhydride copolymer.
[0241] Example 1B
[0242] 91.5 g of water was added to a covered glass bottle, followed by 3.5 g of 25% ammonia water and 5 g of maleic anhydride-styrene copolymer. The bottle cap was tightened and placed in an oven at 95°C. After 4 hours, a uniform 5% polymer solution was obtained.
[0243] Pour 15 ml of polymer solution into a cylindrical aluminum foil spacer with a closed bottom, fix a 10 mL cylindrical glass vial (as a mold) in the center of the aluminum foil spacer, with the periphery and bottom of the glass vial about 9 mm away from the inner wall of the aluminum foil spacer, and keep the top of the glass vial about 1 mm above the solution. Then fix the aluminum foil spacer in the center of a 50 ml (cylindrical) beaker (as a pre-freezing container) containing 20 ml of polymer solution, with the bottom of the spacer about 5 mm away from the beaker. Place it in a -30 ° C refrigerator and freeze it for 2 hours. Transfer the frozen sample to a freeze dryer (below -30 ° C, below 10 Pa) and freeze-dry it for 72 hours, then take out the obtained water-soluble polymer.
[0244] The water-soluble polymer is placed in an oven at 180° C. for heat treatment for 2 hours to dehydrate and deaminate the polymer so that maleimide-based polymer aerogels (ie, the polymer aerogels of the present invention) are obtained on both the inner and outer layers.
[0245] Infrared spectroscopy and proton nuclear magnetic resonance spectroscopy confirmed the presence of maleimide structures in the polymer aerogel. Testing revealed that, based on the total molar weight of maleic anhydride- and maleimide-containing structural units in the polymer aerogel as 100%, the molar ratio of the maleimide-containing structural units was 43.6%. The polymer aerogel exhibited a water contact angle of 138.1°, a thermal conductivity of 0.0362 W / (m·k), and a density of 72.3 kg / m 3 .
[0246] 11 ml of dodecane phase change material was injected into the inner layer of the aerogel until it was filled with excess phase change material. The aerogel phase change composite material was inverted and wiped to obtain a maleimide copolymer aerogel phase change cold storage material.
[0247] When in use, vaccines and the like can be placed in glass bottles.
[0248] Example 2B
[0249] Take 91.5g of water and add it to a covered glass bottle. Then add 3.5g of 25% ammonia water and 5g of maleic anhydride-styrene copolymer. After tightening the cap of the glass bottle, place it in an oven and maintain it at 95°C. After 4 hours, take it out to obtain a uniform 5% mass fraction polymer solution.
[0250] Pour 15 ml of polymer solution into a polytetrafluoroethylene cylindrical container (capacity 25 ml) with a copper bottom, fix a 10 ml cylindrical glass vial (as a mold) in the center of the polytetrafluoroethylene cylindrical container, and keep the distance between the periphery and the bottom of the glass vial and the inner wall of the polytetrafluoroethylene cylindrical container about 9 mm, and keep the top of the glass vial about 1 mm above the solution. Then place the polytetrafluoroethylene cylindrical container on a copper column immersed in liquid nitrogen. After sufficient freezing, remove the ice column of the frozen polymer solution and transfer it to a cylindrical aluminum foil spacer. Then fix the aluminum foil spacer in the center of a 50 ml cylindrical beaker (as a pre-freezing container) containing 20 ml of polymer solution, and keep the bottom of the spacer about 5 mm away from the beaker. Place it in a -30 ° C refrigerator and freeze for 2 hours. Transfer the frozen sample to a freeze dryer (below -30 ° C, below 10 Pa) and freeze-dry it for 72 hours, and then take out the obtained water-soluble polymer.
[0251] The water-soluble polymer is placed in an oven at 180° C. for heat treatment for 2 hours to dehydrate and deaminate so that maleimide-based polymer aerogels are obtained in both the inner and outer layers, and the inner layer maleimide-based polymer aerogel is anisotropic.
[0252] 11 ml of dodecane phase change material was injected into the inner layer of the aerogel until it was filled with excess phase change material. The aerogel phase change composite material was inverted and wiped to obtain a maleimide copolymer aerogel phase change cold storage material.
[0253] Example 3B
[0254] In Example 1B, the steps in the polymer solution preparation process were changed as follows: 94.9 g of water was added to a covered glass bottle, and then 2.1 g of 25% by mass ammonia water and 3 g of maleic anhydride-styrene copolymer were added. The glass bottle cap was tightened and placed in an oven maintained at 95° C. After 4 hours, a uniform 3% by mass polymer solution was obtained. The other preparation steps were the same as in Example 1B, wherein the amount of dodecane added was 11 ml.
[0255] Example 4B
[0256] The dodecane in Example 2B was replaced by tetradecane, and the other preparation steps were the same as those in Example 2B.
[0257] Example 5B
[0258] 80 g of water was added to a reactor with a polytetrafluoroethylene liner, followed by the addition of 3.5 g of 25% ammonia water and 5 g of maleic anhydride isobutylene copolymer (Kuraray ISOBAM-08, molecular weight approximately 300,000). The reactor was sealed and placed in an oven maintained at 95°C. After 4 hours, a uniform polymer solution was obtained, which was then dried at room temperature to obtain a polymer containing maleamic acid and ammonium maleate groups.
[0259] Take 1g of the above polymer and put it into a glass bottle with a lid, add 98.96g of water, and then add 0.04g of 25% ammonia water. After tightening the lid of the glass bottle, put it into an oven and maintain it at 20°C. After 0.5 hours, take it out to obtain a uniform 1% mass fraction polymer solution.
[0260] 15 ml of the polymer solution was poured into a sealed cylindrical aluminum foil spacer. A 10 ml cylindrical glass vial (serving as a mold) was fixed to the center of the aluminum foil spacer, with the perimeter and bottom of the glass vial approximately 9 mm from the inner wall of the aluminum foil spacer, and the top of the glass vial maintained approximately 1 mm above the solution. The aluminum foil spacer was then fixed to the center of a 50 ml polytetrafluoroethylene cylindrical container containing 20 ml of the 0.5% polymer solution prepared in Example 1B, with the bottom of the spacer approximately 5 mm from the bottom of the polytetrafluoroethylene cylindrical container. The container was then placed on a copper column in a liquid nitrogen bath. After pre-freezing, the container was placed in a freeze dryer (below -30°C, below 10 Pa) and freeze-dried for 72 hours to obtain an anisotropic water-soluble polymer. The water-soluble polymer was then heat-treated in an oven at 130°C for 2 hours to dehydrate and deaminize the polymer to obtain a maleimide-based polymer aerogel. 11 ml of dodecane phase change material was injected into the inner layer of the aerogel until it was filled with excess phase change material. The aerogel phase change composite material was inverted and wiped to obtain a maleimide copolymer aerogel phase change cold storage material.
[0261] The leakage rate, phase change temperature and phase change latent heat tested are close to those of Example 2B.
[0262] Example 6B
[0263] 80 g of water was added to a reactor with a polytetrafluoroethylene liner, followed by the addition of 3.5 g of 25% ammonia water and 5 g of maleic anhydride isobutylene copolymer (Kuraray ISOBAM-08, molecular weight approximately 300,000). The reactor was sealed and placed in an oven maintained at 95°C. After 4 hours, a uniform polymer solution was obtained, which was then dried at room temperature to obtain a polymer containing maleamic acid and ammonium maleate groups.
[0264] Take 91.5g of water and add it to a covered glass bottle, then add 3.5g of 25% ammonia water and 5g of the polymer containing maleamic acid and ammonium maleate groups obtained above. After tightening the glass bottle cap, place it in an oven and maintain it at 150°C. After 10 hours, take it out to obtain a uniform 5% mass fraction copolymer aqueous solution.
[0265] The 15 ml polymer solution in Example 2B was replaced with the 5% copolymer solution in this example, and the other preparation steps were the same as those in Example 2B.
[0266] The maleimide polymer aerogel obtained by dehydration and deamination was tested, and then the phase change material was injected according to the steps of Example 2B.
[0267] Infrared spectroscopy and proton nuclear magnetic resonance spectroscopy confirmed the presence of maleimide structures in the polymer aerogel. Testing revealed that, based on the total molar weight of maleic anhydride- and maleimide-containing structural units in the polymer aerogel as 100%, the molar ratio of the maleimide-containing structural units was 38.7%. The polymer aerogel exhibited a water contact angle of 127.6°, a thermal conductivity of 0.0369 W / (m·k), and a density of 73.1 kg / m 3 .
[0268] The leakage rate, phase change temperature and phase change latent heat tested on the phase change material are close to those in Example 2B.
[0269] Recovery Example B
[0270] 5 g of the aerogel phase change material prepared in Example 2B was placed in a sealed glass bottle with a lid, and 1 g of 25% ammonia water and 15 g of water were added. The mixture was kept in an oven at 95 degrees Celsius for 2 h to obtain a liquid (a in Figure 6). The liquid was separated using a separatory funnel to obtain a recovered polymer aqueous solution (c in Figure 6) and a phase change material (b in Figure 6).
[0271] The obtained polymer aqueous solution was used as the raw material for preparing aerogel, and the phase change material was used as the raw material for preparing phase change material, and a phase change composite material was prepared according to the method of Example 2B.
[0272] The leakage rate, phase change temperature and phase change latent heat tested are close to those of Example 2B.
[0273] Table 1B
[0274] As can be seen from Table 1B, the adsorption capacity of the phase change material in the recyclable cold storage phase change composite material in the embodiment of the present invention is relatively high, and the leakage of the phase change material is relatively small, and it can be widely used in the fields of food preservation and cold chain transportation (such as cold chain transportation of vaccines and medicines).
[0275] Table 2B
[0276] As can be seen from Table 2B, the porous aerogel in the present invention causes very little latent heat loss to the phase change material, and a phase change composite material with high cold storage capacity and low leakage can be prepared.
[0277] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation of the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein. On the contrary, the present invention can be extended to all other methods and applications with the same function.
[0278] All publications, patent applications, patents, and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of conflict, the definitions in this specification shall prevail.
[0279] When this specification uses the prefix "well known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, the objects introduced by the prefix include those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become generally recognized in the art to be suitable for similar purposes.
[0280] The endpoints and any values of the ranges disclosed in this application document are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and a separate point value, and the separate point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be considered as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be considered as specifically disclosed in this article.
[0281] In the context of this specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.
[0282] Moreover, any embodiment described herein may be freely combined with one or more other embodiments described herein, and the technical solutions or technical ideas thus formed shall be deemed as part of the original disclosure or original record of the present invention, and shall not be regarded as new content that has not been disclosed or anticipated herein, unless a person skilled in the art considers that the combination is obviously unreasonable.
Claims
1. A polymer aerogel, wherein the polymer comprises a structural unit containing a maleic anhydride group and a structural unit containing a maleimide group, wherein the maleic anhydride group is The maleimide group refers to 2. The polymer aerogel according to claim 1, characterized in that: Based on the total molar amount of the structural units containing maleic anhydride groups and the structural units containing maleimide groups as 100%, the molar ratio of the structural units containing maleimide groups in the polymer is 5%-70%, preferably 10%-60%; more preferably 20%-50%.
3. The polymer aerogel according to claim 1, wherein: The polymer is derived from a polymer raw material containing one or more structural units containing maleic anhydride, maleimide, maleic acid and ammonium salt, maleamic acid and ammonium salt groups; preferably, the polymer raw material is a copolymer of a polymerization monomer including one or more polymerization monomers of maleic anhydride, maleimide, maleic acid and ammonium salt, maleamic acid and ammonium salt and an olefin monomer; more preferably, the olefin monomer is at least one of α-methylstyrene, styrene, and isobutylene.
4. The polymer aerogel according to claim 1, wherein: The polymer aerogel can be dissolved in ammonia water at 0-150° C. to form a polymer aqueous solution; preferably, the polymer aqueous solution can be recovered to obtain the polymer aerogel after pre-freezing, freeze-drying, and heat treatment; and / or, The thermal conductivity of the polymer aerogel is 0.025-0.05 W / (m·k), preferably 0.027-0.04 W / (m·k); and / or, The density of the polymer aerogel is 10-100 kg / m 3 , preferably 15-75kg / m 3 and / or, The polymer aerogel is a three-dimensional porous material.
5. The polymer aerogel according to claim 1, wherein: The static water contact angle of the polymer aerogel is above 100°, preferably above 110°, more preferably above 135°; and / or, The polymer aerogel is insoluble in water. Preferably, the polymer aerogel will not dissolve to form a polymer aqueous solution after being immersed in water at 20-40° C. for 24 hours, preferably for 72 hours, and more preferably for 168 hours.
6. The polymer aerogel according to any one of claims 1 to 5, characterized in that: The polymer aerogel is prepared by reacting a polymer raw material containing one or more structural units of maleic anhydride, maleimide, maleic acid and ammonium salt, or maleamic acid and ammonium salt groups with ammonia water in a sealed condition, and then pre-freezing, freeze-drying, and heat-treating for dehydration and deamination.
7. A method for preparing the polymer aerogel according to any one of claims 1 to 6, comprising reacting a polymer raw material containing one or more structural units selected from the group consisting of maleic anhydride, maleimide, maleic acid and ammonium salt, or maleamic acid and ammonium salt with aqueous ammonia under closed conditions, followed by pre-freezing, freeze-drying, and heat treatment for dehydration and deamination to obtain the polymer aerogel.
8. The preparation method according to claim 7, characterized in that The specific steps include: (1) reacting the polymer raw material with ammonia water under closed conditions to obtain a polymer aqueous solution; (2) pre-freezing the polymer aqueous solution obtained in step (1), and then freeze-drying it to obtain a water-soluble polymer; (3) heat-treating the water-soluble polymer obtained in step (2) to obtain the polymer gas condensate glue.
9. The preparation method according to claim 8, characterized in that: In step (1): Based on the total mass of the reaction system as 100%, the mass fraction of the polymer raw material used is 0.1%-30%, preferably 0.5%-10%, more preferably 1%-5%, and based on the mass of ammonia in the ammonia water, the mass fraction of ammonia used is 0.0001%-30%, preferably 0.01%-10%, more preferably 0.1%-1%, and the remaining components are water; And / or, the reaction conditions include: The reaction temperature is 0-200° C., preferably 50-150° C., more preferably 80-100° C.; and / or the reaction time is 0.01-100 h, preferably 0.5-10 h, more preferably 1-5 h.
10. The preparation method according to claim 8, characterized in that: In step (2): Pre-freezing the polymer aqueous solution obtained in step (1) in a mold, preferably, the cooling source temperatures of the solution in all directions during the pre-freezing are the same or different; and / or, The freeze-drying conditions include: the temperature is preferably below (-10)°C; and the vacuum degree is preferably below 1000 Pa.
11. The preparation method according to claim 8, characterized in that: The conditions for heat treatment in step (3) include: The temperature is 100-300° C., preferably 130-200° C., more preferably 150-190° C., and / or the time is 0.1-10 h, preferably 0.5-3 h, more preferably 1-2 h.
12. The preparation method according to any one of claims 7 to 11, characterized in that: The polymer raw material is a copolymer of one or more polymer monomers selected from maleic anhydride, maleimide, maleic acid and ammonium salt, maleamic acid and ammonium salt, and olefin monomers; preferably, the olefin The monomer includes at least one of α-methylstyrene, styrene, and isobutylene.
13. The preparation method according to any one of claims 7 to 11, characterized in that: The polymer raw material is at least one of styrene maleic anhydride copolymer, styrene maleic anhydride vinyl silicone oil copolymer, and maleic anhydride isobutylene copolymer; preferably, the polymer raw material is at least one of styrene maleic anhydride copolymer and maleic anhydride isobutylene copolymer.
14. A method for recovering a polymer aerogel, wherein the polymer aerogel is the polymer aerogel according to any one of claims 1 to 6 or the polymer aerogel prepared by the preparation method according to any one of claims 7 to 13, the method comprising mixing the polymer aerogel and / or a material containing the polymer aerogel with aqueous ammonia under closed conditions until an aqueous solution containing the recovered polymer is obtained, and optionally removing insoluble matter to obtain an aqueous solution of the recovered polymer. Preferably, the temperature of the mixing reaction is 0-200° C., preferably 50-150° C., more preferably 80-100° C., and / or the time of the mixing reaction is 0.01-100 h, preferably 0.5-10 h, more preferably 1-5 h.
15. The recycling method according to claim 14, characterized in that: The recovery method further comprises pre-freezing, freeze-drying, and heat-treating the aqueous solution of the recovered polymer to obtain the polymer aerogel; preferably, During the pre-freezing, the temperatures of the cold sources of the solution in all directions are the same or different; and / or, Freeze-drying conditions include: temperature below (-10)°C; and / or, vacuum degree below 1000Pa; and / or, Heat treatment conditions include: The temperature is 100-300° C., preferably 130-200° C., more preferably 150-190° C., and / or the time is 0.1-10 h, preferably 0.5-3 h, more preferably 1-2 h.
16. The recycled polymer aerogel obtained by the recycling method according to claim 14 or 15.
17. Use of the polymer aerogel according to any one of claims 1 to 6, the polymer aerogel prepared by the preparation method according to any one of claims 7 to 13, or the recycled polymer aerogel according to claim 16 as a porous material, preferably as a carrier, a filter material, for adsorbing organic phase change materials, or as an oil-water separation material or thermal insulation material.
18. A recyclable cold storage phase change composite material, comprising a polymer aerogel and a phase change material loaded in the polymer aerogel; wherein: The polymer aerogel is the polymer aerogel according to any one of claims 1 to 6, the polymer aerogel prepared by the preparation method according to any one of claims 7 to 13, or the recycled polymer aerogel according to claim 16.
19. The recyclable cold storage phase change composite material according to claim 18, characterized in that: Based on the total mass of the recyclable cold storage phase change composite material as 100%, the content of the polymer aerogel is 2%-20%, preferably 4%-10%, and the content of the phase change material is 80%-98%, preferably 90%-96%; and / or, The phase change material is an organic phase change material. Preferably, the phase change temperature of the organic phase change material is (-10)-30°C, and / or the phase change latent heat is 55-280 J / g; more preferably, the organic phase change material is an alkane organic phase change material; most preferably, at least one of decane, dodecane, and tetradecane; and / or, Under the temperature condition that the phase change material is in liquid state, the leakage amount of the phase change material in the recyclable cold storage phase change composite material is less than 10 wt%, preferably less than 5 wt%, and more preferably less than 2 wt%.
20. The recyclable cold storage phase change composite material according to claim 18, characterized in that: The polymer aerogel is an anisotropic aerogel, preferably an anisotropic aerogel obtained by using a unidirectional cold source with different temperatures during pre-freezing; and / or, The polymer aerogel can be dissolved in ammonia water at 0-150° C. to form a solution containing the polymer. Preferably, the solution containing the polymer can be recovered to obtain the polymer aerogel by pre-freezing, freeze-drying, and heat treatment; and / or, The density of the polymer aerogel is 100 kg / m 3 Below, preferably 15-80kg / m 3 .
21. The recyclable cold storage phase change composite material according to any one of claims 18 to 20, characterized in that: The polymer aerogel is prepared by reacting a polymer raw material containing one or more structural units of maleic anhydride, maleimide, maleic acid and ammonium salt, or maleamic acid and ammonium salt groups with ammonia water in a sealed environment, and then pre-freezing, freeze-drying, and heat-treating for dehydration and deamination; preferably, During pre-freezing, the temperature of the cooling source in each direction of the solution is the same or different. More preferably, the temperature of the cooling source in each direction of the solution is different during pre-freezing, thereby obtaining anisotropic aerogel. Most preferably, the pre-frozen solution has a different unidirectional cold source temperature to obtain anisotropic aerogel.
22. A method for preparing the recyclable cold storage phase change composite material according to any one of claims 18 to 21, comprising loading the phase change material in the polymer aerogel.
23. The preparation method according to claim 22, characterized in that The preparation method comprises the following steps: (1) reacting a polymer raw material containing one or more structural units selected from the group consisting of maleic anhydride, maleimide, maleic acid and ammonium salt, and maleamic acid and ammonium salt with aqueous ammonia in a sealed environment to obtain a polymer aqueous solution; (2) pre-freezing the polymer aqueous solution obtained in step (1), and then freeze-drying it to obtain a water-soluble polymer; (3) heat-treating the water-soluble polymer obtained in step (2) to obtain the polymer aerogel; (4) Loading the phase change material in the polymer aerogel.
24. The preparation method according to claim 23, characterized in that: In step (1), based on the total mass of the reaction system as 100%, the mass fraction of the polymer raw material used is 0.1%-30%, preferably 1%-10%, more preferably 2%-5%, and based on the mass of ammonia in ammonia water, the mass fraction of ammonia used is 0.001%-30%, preferably 0.01%-10%, more preferably 0.1%-1%, and the remaining components are water; and / or, In the pre-freezing stage, the temperature of the cooling source in each direction of the polymer aqueous solution obtained in step (1) is different, preferably the temperature of the cooling source in one direction is different; and / or, Before pre-freezing in step (2), the mold is inserted into the polymer aqueous solution obtained in step (1), and after the heat treatment in step (3), the mold is optionally removed to obtain a polymer aerogel having a cavity. In step (4), the phase change material is loaded into the polymer aerogel.
25. A recyclable cold storage phase change material with a real-time temperature monitoring function, the recyclable cold storage phase change material having a layered structure, comprising an inner layer formed by the recyclable cold storage phase change composite material according to any one of claims 18 to 21 or a recyclable cold storage phase change composite material prepared by the preparation method according to any one of claims 22 to 24, and an outer layer formed by a second polymer aerogel.
26. The recyclable cold storage phase change material with real-time temperature monitoring function according to claim 25, characterized in that: The thickness of the inner layer is greater than 3 mm, and the thickness of the outer layer is greater than 5 mm; and / or, There is also a spacer layer between the inner layer and the outer layer; and / or, The inner layer is provided with a cavity; and / or, The second polymer aerogel has photoluminescence properties and can change the light signal with changes in temperature; preferably, the second polymer aerogel is selected from at least one polymer aerogel having photoluminescence properties and can change the light signal with changes in temperature in the recyclable cold storage phase change composite material according to any one of claims 18 to 21, and the second polymer aerogel may be the same as or different from the polymer aerogel in the recyclable cold storage phase change composite material; More preferably, the second polymer is a copolymer formed by styrene and one or more polymerizable monomers selected from the group consisting of maleic anhydride, maleimide, maleic acid and ammonium salt, maleamic acid and ammonium salt.
27. A method for preparing a recyclable cold storage phase change material with real-time temperature monitoring function according to claim 25 or 26, characterized in that The following steps are involved: (1) reacting a polymer raw material containing one or more structural units selected from the group consisting of maleic anhydride, maleimide, maleic acid and ammonium salt, and maleamic acid and ammonium salt with aqueous ammonia in a sealed environment to obtain a polymer aqueous solution; (2) placing the polymer aqueous solution in the space inside the spacer layer or in the space between the inner side of the spacer layer and the mold, and then pre-freezing it, and then freeze-drying it to obtain a water-soluble polymer; (3) heat-treating the water-soluble polymer obtained in step (2), and optionally removing the mold to obtain a polymer aerogel having a cavity; (4) loading a phase change material into the polymer aerogel obtained in step (3) to form an inner layer of the recyclable cold storage phase change material; wherein, in step (2), step (3), step (4) and / or between the steps and / or after step (4), the second polymer aerogel is coated on the outside of the spacer layer, thereby forming the outer layer of the recyclable cold storage phase change material; Alternatively, in step (2), an aqueous solution containing a second polymer aerogel and / or a second polymer aqueous solution is placed in the space outside the spacer layer to form the outer layer of the recyclable cold storage phase change material; preferably, the second polymer aqueous solution is the same as the polymer aqueous solution in step (1).
28. The preparation method according to claim 27, characterized in that: The mass fraction of the polymer content in the inner layer polymer aqueous solution is 0.1%-30%, preferably 1%-10%, and / or the mass fraction of the second polymer content in the aqueous solution of the second polymer aerogel and / or the second polymer aqueous solution is each 0.1%-30%, preferably 0.5%-10%, more preferably 1%-5%; and / or, In step (2), during the pre-freezing stage, the temperature of the cooling source in each direction of the polymer aqueous solution obtained in step (1) is different, preferably the temperature of the cooling source in one direction is different.
29. Application of the recyclable cold storage phase change composite material according to any one of claims 18 to 21, or the recyclable cold storage phase change composite material prepared by the preparation method according to any one of claims 22 to 24, the recyclable cold storage phase change material with real-time temperature monitoring function according to claim 25 or 26, or the recyclable cold storage phase change material with real-time temperature monitoring function prepared by the preparation method according to claim 27 or 28 in the fields of food preservation and cold chain transportation.